Collaborative Human- Robot System for HALS Suture Procedures - Bauzano-Núñez, Enrique; Estébanez-Campos, María Belén; García-Morales, Isabel; Muñoz-Martínez, Víctor Fernando (IEEE, 2016)
Over the last years, minimally invasive surgery (MIS) has continuously improved due to new techniques and technologies. One of these novel techniques is hand-assisted laparoscopic surgery (HALS), where the surgeon inserts one hand through a small incision inside the abdominal cavity of the patient. As this kind of intervention only allows the use of one laparoscopic tool, the surgeon requires a deep collaboration with the assistant in order to coordinate their movements for performing a surgical maneuver. In this way, the replacement of a human assistant with a robot system specifically designed for HALS must include a natural human–machine interface and the capability for taking autonomous decisions. These features need the implementation of a model of the surgical protocol, a system capable of recognizing the corresponding surgical gestures made by the surgeon, and an autonomous task system that assists the surgeon without his direct intervention. This paper is focused on the design of a collaborative surgical robot that implements all the features previously described. This robot assistant has been validated by means of in vitro laparoscopic sutures on a HALS scenario with CISOBOT, a two-arm robotic platform designed and developed at the University of Malaga.
Keywords: Laparoscopia; Force control; human–robot interaction; medical robotics; robot control; robot motion